The influence of knowledge and entrepreneurial orientation on product innovation and financial performance Batik Msme’s: - - Andrias Dwimahendrawan; Ningrum Suryadinata; Ayu Rahmi (Jurnal Mantik, 2024)
Company performance is a measure of a company's success in carrying out business activities. Company performance is the final result of all activities within a company. If the company's performance is poor, it is indirectly very difficult for the company to maintain its existence. Internal factors that influence company performance are company knowledge, entrepreneurial orientation, product innovation and competitive advantage. GoalThe purpose of this research is to analyze the influence of knowledge and entrepreneurial orientation on product innovation, and the role of innovation in mediating the indirect influence of knowledge and entrepreneurial orientation on financial performance. The research location is batik MSME’s in Banyuwangi Bondowoso Regency, and Jember, East Java Province, Indonesia. The number of respondents was 43 units. Analyze data using analysis Generalized Structured Component Analysis (GSCA). The research results show variablesKnowledge and entrepreneurial orientation have a significant positive effect on innovation and financial performance. This indicates that the better the knowledge and entrepreneurial orientation (innovative, proactive, aggressively competitive, brave to take risks, and independent) of batik creative economy business owners, the better the product innovation and financial performance will be